Foraging trip time-activity budgets and reproductive success in the black-legged kittiwake - Chivers, L.S.; Lundy, M.G.; Colhoun, K.; Newton, S.F.; Houghton, Jonathan; Reid, N. (Marine Ecology Progress Series, 2012)
Seabirds are central place foragers during the breeding season and, as marine food resources are often patchily distributed, flexibility in foraging behaviour may be important in maintaining prey delivery rates to chicks. We developed a methodological approach using a combination of GPS data loggers and temperature-depth recorders that allowed us to describe the behaviour of surface-feeding seabirds. Specifically, we tested whether differences in foraging behaviour of black-legged kittiwakes Rissa tridactyla could be linked with reproductive success by comparing 2 consecutive years at 2 sites. At Rathlin Island (Northern Ireland) during 2010, foraging differed markedly from that during 2009 and from that at Lambay Island (Republic of Ireland) during both years. Birds exhibited foraging trips of greater duration, travelled a greater total distance, spent more time in transit and spent longer recuperating on the surface of the water. This notable shift was associated with a decline in breeding success, with greater loss of eggs to predation and lower prey delivery rates, resulting in the starvation of 15 % of chicks. We suggest that food resources were reduced or geographically less accessible during 2010, with suitable foraging areas located further from the colony. Birds did not invest greater amounts of time attempting to catch prey. Thus, our results indicate that kittiwakes at Rathlin modulated their foraging behaviour not by increasing foraging effort through feeding more intensively within prey patches but by extending their range to increase the probability of encountering more profitable prey patches.